Chapter 18 Surgery, Imperial Rule and Colonial Societies (1800-1930) Technical, Institutional and Social Histories - Fitzpatrick, Kieran (Springer Nature, 2018)
The following chapter is concerned with the ways in which political, social and cultural contexts shape the performance and perceptions of surgery, especially under nineteenth-century colonial empires.